The effect of polyethylene glycol structure on paclitaxel drug release and mechanical properties of PLGA thin films - Steele, Terry W. J. (2017)
Thin films of poly(lactic acid-co-glycolic acid) (PLGA) incorporating paclitaxel typically have slow release rates of paclitaxel of the order of 1 μg day−1 cm−2. For implementation as medical devices a range of zero order release rates (i.e. 1–15 μg day−1 cm−2) is desirable for different tissues and pathologies. Eight and 35 kDa molecular weight polyethylene glycol (PEG) was incorporated at 15%, 25% and 50% weight ratios into PLGA containing 10 wt.% paclitaxel. The mechanical properties were assessed for potential use as medical implants and the rates of release of paclitaxel were quantified as per cent release and the more clinically useful rate of release in μg day−1 cm−2. Paclitaxel quantitation was correlated with the release of PEG from PLGA, to further understand its role in paclitaxel/PLGA release modulation. PEG release was found to correlate with paclitaxel release and the level of crystallinity of the PEG in the PLGA film, as measured by Raman spectrometry. This supports the concept of using a phase separating, partitioning compound to increase the release rates of hydrophobic drugs such as paclitaxel from PLGA films, where paclitaxel is normally homogeneously distributed/dissolved. Two formulations are promising for medical device thin films, when optimized for tensile strength, elongation, and drug release. For slow rates of paclitaxel release an average of 3.8 μg day−1 cm−2 using 15% 35k PEG for >30 days was achieved, while a high rate of drug release of 12 μg day−1 cm−2 was maintained using 25% 8 kDa PEG for up to 12 days.